2014
DOI: 10.1039/c4cc04594g
|View full text |Cite
|
Sign up to set email alerts
|

Conformal sulfated zirconia monolayer catalysts for the one-pot synthesis of ethyl levulinate from glucose

Abstract: Here we describe a simple route to creating conformal sulphated zirconia monolayers throughout an SBA-15 architecture that confers efficient acid-catalysed one-pot conversion of glucose to ethyl levulinate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 24 publications
2
75
0
Order By: Relevance
“…[103] In the case of glucose, ethyl glycoside is mainly formed, except from sulfated zirconia, which gives an efficient quantity of ethyl levulinate owing to its Lewis acids ites that can promote glucose isomerization to fructose. Recently,W ilson et al [105] have reported the use of sulfated zirconia fort he one-pot synthesis of ethyl levulinate from glucose. The yield of ethyl levulinate is dependento nt he reactiont emperature, and the highesty ield is obtained at 140-150 8C.…”
Section: Heterogeneous Esterificationmentioning
confidence: 99%
See 1 more Smart Citation
“…[103] In the case of glucose, ethyl glycoside is mainly formed, except from sulfated zirconia, which gives an efficient quantity of ethyl levulinate owing to its Lewis acids ites that can promote glucose isomerization to fructose. Recently,W ilson et al [105] have reported the use of sulfated zirconia fort he one-pot synthesis of ethyl levulinate from glucose. The yield of ethyl levulinate is dependento nt he reactiont emperature, and the highesty ield is obtained at 140-150 8C.…”
Section: Heterogeneous Esterificationmentioning
confidence: 99%
“…The appearance of polymer degradation products (i.e.,h umins)i sr eported at highert emperatures. [105] Theu se of zeolitesa nd mesoporous (SO 3 H) functionalized carbon/silica composites for the efficient conversion of glucose [105] and fructose [106] into ethyl levulinate hasa lso been studied by Wilson and Valente, respectively.…”
Section: Heterogeneous Esterificationmentioning
confidence: 99%
“…For this reason, researchers developed another new and efficient approach to produce levulinate esters by the alcoholysis of cellulosic biomass or carbohydrates under acidic conditions [13][14][15]. Among various solid acid catalysts, sulfated metal oxides have been widely utilized to convert carbohydrates, such as sulfated titania, and zirconia [16,17]. However, there are still considerable opportunities to improve the catalytic activity and optimize the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…EL synthesis from carbohydrates such as glucose was studied over various catalysts such as HCl, H 3 PO 4 , H 2 SO 4 , H 2 SO 4 –Al(OTf) 3 , SO 4 2− –ZrO 2 , SO 4 2− –ZrO 2 /SBA‐15, Amberlyst‐35, and HUSY (zeolite) . Among homogenous catalyst, H 2 SO 4 ‐Al(OTf) 3 having both Brønsted and Lewis acidity showed 64.9% EL at 180°C in 3 h , and heterogeneous catalysts such as HUSY showed maximum yield EL (41%) at 160°C in 20 h .…”
Section: Introductionmentioning
confidence: 99%